Bone Turnover Markers - Clementine YF Yap MSc, DLM(ASCP); Tar Choon Aw FRCP (Edin), FRCPA (Proceedings of Singapore Healthcare, 2010)
Bone turnover markers (BTM) provide useful data to titrate the optimal dosing regimes for patients within 3–6 months as compared to 1–2 years using bone mineral density (BMD). Serum obtained under standardised conditions (fasting, early morning) should be tested using a precise automated immunoassay for a panel of bone markers that includes a resorption marker — C-terminal cross-linked telopeptide of bone collagen (CTX) — and formation markers — Procollagen Type 1 N-terminal Propeptide (P1NP) and Osteocalcin (OC).